Respiratory Failure in Premature Babies Born from Multiple Pregnancy - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz (Общая реаниматология)
Objective: to reveal the factors that are responsible for the development of respiratory distress syndrome (RDS) and the specific features of its course in preterm twin neonates. Subjects and methods. Twenty-three patients who had had twin pregnancy, including 9 (39.1%) and 14 (60%) with monochorial and bichorial biamniotic twin pregnancies, respectively, were examined. Their mean age was 28.5±5.4 years. Obstetric and gynecologic histories, conditions at conception, the course of pregnancy, the type of pla-centation, and fetal presentation were considered. The placentas were morphologically examined. In all the patients, pregnancy ended in birth of 46 premature neonates, of them there were 19 (41.3%) boys and 27 (58.7%) girls. The gestational age of the neonates averaged 31.7±2.3 weeks. The evaluation of the efficiency of performed therapy used clinical assessment of the status of the premature neonates; measurement of partial oxygen tension (pO2) and calculation of alveolar-arterial oxygen gradient (A-a DO2), respiratory index (RI), and oxygenation index (OI); death rates were analyzed. Results. The main cause of respiratory failure (RF) was RDS in premature twins. Neonatal blood aspiration-caused pneumonia occurred in one case. The course of RDS was variable. Most neonatal infants needed exogenous surfactant replacement therapy and mechanical ventilation (MV). No signs of RF were present in 7 (15.2%) premature neonates. Conclusion. Premature twins are a high RDS risk group. The unfavorable factors that contribute to the development of the disease are multiple pregnancy, a past maternal obstetric history, in-vitro fertilization-induced pregnancy, severe gestosis in the second half of pregnancy, and preterm delivery. The type of placentation affects the fetal status after birth. Fatal outcome occurred in infants from the monochorial bioamniotic twins. In multiple pregnancies, there are pathological changes in the placenta, its membranes, and umbilical cord, which induces fetal circulatory disorders and creates unfavorable conditions for untrauterine development of the fetal lung. In premature twins, MV considerably varies in duration: from short-term to long-term, which is suggestive of the severe course of RDS in a number of cases despite the administration of a surfactant. Hgh neonata! RSD death rates recorded in the twins. Key words: premature neonates, respiratory distress syndrome, surfactant, mechanical ventilation, multiple pregnancy, type of placentation.